2011
DOI: 10.1002/jbm.b.31976
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Portland cement porous scaffolds for load‐bearing bone tissue engineering applications

Abstract: Modified Portland cement porous scaffolds with suitable characteristics for load-bearing bone tissue engineering applications were manufactured by combining the particulate leaching and foaming methods. Non-crosslinked polydimethylsiloxane was evaluated as a potential reinforcing material. The scaffolds presented average porosities between 70 and 80% with mean pore sizes ranging from 300 μm up to 5.0 mm. Non-reinforced scaffolds presented compressive strengths and elastic modulus values of 2.6 and 245 MPa, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
(58 reference statements)
1
11
0
1
Order By: Relevance
“…on the concentration of the seeded cells (21), which justifies the greater activity of this enzyme in the final period of evaluation (7 days). In the other evaluated lines, there was no significant difference among the time intervals.…”
Section: Discussionmentioning
confidence: 96%
“…on the concentration of the seeded cells (21), which justifies the greater activity of this enzyme in the final period of evaluation (7 days). In the other evaluated lines, there was no significant difference among the time intervals.…”
Section: Discussionmentioning
confidence: 96%
“…The cell viability was calculated as the sample absorption at 570 nm divided by the absorption of the control group at the same wavelength. 19.0 (SPSS, Chicago, IL, U.S.A.) was used to analyze our data. The results are reported as mean 6 standard deviation.…”
Section: Cytotoxicity Test Of Ra On Osteoblast Cellsmentioning
confidence: 99%
“…Moreover, the Ca(OH)2 released under physiological conditions interacts with phosphates in the medium to produce rapid precipitation of amorphous apatite. However, previous research by Gallego-Perez, et al showed that the showed that the Ca(OH)2 present in hydrated Portland cement could be extremely cytotoxic [146,147]. Such toxic effect effect may not be desirable in certain applications, like implants, as it will prevent adequate cell adhesion and propagation on the surface and cause the formation of a large necrotic zone around the implant after placement, provoking a chronic inflammatory response by the host, which could potentially lead to total rejection of the implant.…”
Section: Bioactive Micropatterned Surfacesmentioning
confidence: 97%
“…To avoid this, Gallego-Perez, et al developed a simple strategy to obtain cytocompatible Portland cement based on the carbonation of the paste. The CO2 introduced during the hydration of Portland cement reacts with the Ca(OH)2 that is being formed to produce calcium carbonate (CaCO3), which decreases the pH of the cement (~7.4), and provides a more compatible environment for cell growth [146,147,151]. More recently, a new method was developed ( Figure 10) for the production of cytocompatible Portland cement microparticles, which could be incorporated, along with nano-hydroxyapatite particles, in micropatterned bioactive coatings (Figure 9c-f) of interest to dental implantology [148][149][150].…”
Section: Bioactive Micropatterned Surfacesmentioning
confidence: 99%